Effect of flavour manipulation on low and high-frequency waterpipe users' puff topography, toxicant exposures and subjective experiences. (20th July 2019) - Maziak, Wasim; Ben Taleb, Ziyad; Ebrahimi Kalan, Mohammad; Ward-Peterson, Melissa; Bursac, Zoran; Osibogun, Olatokunbo; Eissenberg, Thomas
Abstract : Background: Flavoured tobacco is one of the major factors behind the popularity of waterpipe (WP) smoking in the USA and internationally. The current study examined the impact of flavour manipulation on satisfaction, puff topography and toxicant exposure among high-frequency and low-frequency WP users. Method: This cross-over study was conducted among 144 current (past month) WP smokers reporting WP smoking less than once a week (low-frequency users; n=69) or at least once a week (high-frequency users; n=75) in the past 6 months. Participants attended two counterbalanced 45 min ad libitum smoking sessions that differed by flavour (preferred flavoured vs unflavoured tobacco), preceded by ≥12 hours of tobacco use abstinence. Outcome measures included puff topography, expired carbon monoxide (eCO), plasma nicotine and subjective measures. Results: Both high-frequency and low-frequency WP users reported an enhanced smoking experience and greater interest in future use after smoking the flavoured compared with unflavoured tobacco (p<0.05 for all). High-frequency users, however, were more keen on smoking the flavoured tobacco in the future, had higher puffing parameters in general compared with low-frequency users (p<0.05 for all) and had no differences in eCO and plasma nicotine concentrations between the flavoured and unflavoured tobacco conditions (p>0.05 for all). On the other hand, low-frequency users had significantly greater eCO and plasma nicotine concentrations following smoking the unflavoured compared with flavoured tobacco condition (p<0.05 for all). Conclusions: Our results indicate that removing flavours will likely negatively affect WP satisfaction and future use and that such an effect will be more pronounced among high-frequency compared with low-frequency WP smokers.